1997
DOI: 10.1001/jama.1997.03540380041029
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Maintenance of Normothermia Reduces the Incidence of Morbid Cardiac Events

Abstract: In patients with cardiac risk factors who are undergoing noncardiac surgery, the perioperative maintenance of normothermia is associated with a reduced incidence of morbid cardiac events and ventricular tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
205
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,066 publications
(224 citation statements)
references
References 49 publications
2
205
1
8
Order By: Relevance
“…Recent studies showed that perioperative hypothermia occurs in more than 70% of patients in the perioperative phase and can lead to several complications: increase in blood loss during surgery by impairing platelet function and clotting factor enzyme function, increase in the incidence of surgical wound infection induced by peripheral vasoconstriction with a significant reduction of subcutaneous oxygen tension and an impairment in immune function, increase in heart rate and oxygen demand in the presence of shivering [23-25]. Additionally Frank et al reported a higher prevalence of myocardial ischemia and ventricular tachycardia in patients with perioperative hypothermia [26]. Otherwise during HITHOC temperature in the pleural space rises up to about 42°C with the risk of systemic hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that perioperative hypothermia occurs in more than 70% of patients in the perioperative phase and can lead to several complications: increase in blood loss during surgery by impairing platelet function and clotting factor enzyme function, increase in the incidence of surgical wound infection induced by peripheral vasoconstriction with a significant reduction of subcutaneous oxygen tension and an impairment in immune function, increase in heart rate and oxygen demand in the presence of shivering [23-25]. Additionally Frank et al reported a higher prevalence of myocardial ischemia and ventricular tachycardia in patients with perioperative hypothermia [26]. Otherwise during HITHOC temperature in the pleural space rises up to about 42°C with the risk of systemic hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly our findings are consistent with other studies where the creation of a humified CO 2 atmosphere in the surgical wound cavity increased the total wound temperature by 0.5 °C [6]. Whilst such changes may appear insignificant, mild hypothermia has been associated with surgical-wound infection [22, 23], adverse effects on the coagulation system [24], platelet dysfunction [25], increased increases blood loss and allogeneic transfusion requirements [26], and increase adverse cardiac events [27], all of which can be fatal in the context of OLT. Given the long duration and complexity of liver transplantation surgery as well as a high rate of post-operative complications in this patient group, small differences in temperature may be clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia often causes shivering after anesthesia, which may increase oxygen consumption 3 to 4 times, and increases the risk of ventricular tachycardia and morbid cardiac events [1]. There is a report that body cooling might cause decreased oxygen pressure in the brain tissue when shivering started [12].…”
Section: Problems and Benefits Of Hypothermiamentioning
confidence: 99%